Teaching with compassion : an educator's oath to teach from the heart - Kaufman, Peter, 1967-2018; Schipper, Janine, 1970- (Rowman & Littlefield Publishing Group, Inc., 2018)
"In a world where students are often seen as test scores and not as human beings, where their well-being is challenged by poverty, intolerance, and bullying, and where technological innovations frequently erode genuine personal contact, compassionate teachers are needed more than ever. Teaching with Compassion offers practical tools and strategies designed to help educators foster a culture of care and compassion. Organized around an eight-point "Teaching with Compassion Oath," this book draws on real life examples and exercises to demonstrate the power and potential of teaching from the heart. Written for both experienced and novice educators alike, Teaching with Compassion is sure to stimulate inquiry and provide ongoing inspiration."--Publisher's description.